Pengaruh Inovasi Produk Dan CRM Terhadap Kepuasan Dimediasi Keputusan Pembelian Pada Industri Coffee Shop - Djunaedi Djunaedi; Sati Ratna Dewanti; Sati Ratna Dewanti; Moh. Faris Akbar Alamsyah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to determine the feasibility of boosting the model from the tested constructs covering product innovation (exogenous 1), customer relationship management (exogenous 2), purchase decisions (mediation) and customer satisfaction (endogenous). The research design is explanatory with hypothetical associations. The research method uses partial least square with outer model indicator, inner model and boostrapping model. Research sampling of 150 respondents with inclusion as a step to strengthen the model construct of boostrapping. The resulting assessment with the value of each bosstrapping model showed a significant < 0.05 with an estimated model of 64.4% expressed very good; Rsquare > 0.5 is declared feasible; and the level of importance- performance of the construct of the resulting framework development model reached a satisfaction value of > 0.25. Keywords: Customer Relationship Management; Product Innovation; Purchase Decision; Satisfaction